One Parameter at a time Combinatorial Testing Strategy Based on Harmony Search Algorithm OPAT-HS - Al-Sewari, Abdul Rahman Ahmed Mohammed; Mu’aza, Aminu Aminu; Rassem, Taha H.; Tairan, Nasser M.; Shah, Habib; Kamal Z., Zamli (American Scientific Publisher, 2018)
Software testing is required to verify and validate systems. Combinatorial testing in one of the significant testing techniques. Design and select test cases for combinatorial testing considered as combinatorial problem. Even though there are some existing optimization algorithm based combinatorial testing strategies, that minimize the number of test cases, but most of these strategies based on one-test-at-a-time (OTAT) approach and none of them has adopted the one-parameter-at-a-time (OPAT) approach. Therefore, this paper will propose a new OPAT strategy based on Harmony Search Algorithm (HS) called OPAT-HS. OPAT-HS was originally designed only to support Covering Array (CA) and Mixed Covering Array (MCA) for uniform interaction strength. The result obtained in the experiments appears that OPAT-HS is always best at configurations with MCA notations.